2011
DOI: 10.1093/rheumatology/ker076
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical remodelling of draining lymph node structure in early and established rheumatoid arthritis assessed by power Doppler ultrasonography

Abstract: Draining LNs in RA are subjected to subclinical intra-parenchymal changes and vascular flow modulation detectable by PD-US. Sonographic signs of LN involvement associate with disease activity and are reversible upon treatment. These data point at LN reactivity as a dynamic component of RA inflammatory cascade and an attractive platform to be explored in prognostic and response to therapy evaluations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 21 publications
(30 reference statements)
2
35
0
Order By: Relevance
“…In contrast, we predict that RA flares that take place sporadically in patients with chronic disease are associated with the loss of lymphatic egress from joints, and can be assessed by “collapsed” efferent LN and the absence of a lymphatic pulse. With the recent development of clinical PD-US [41] and NIR-ICG [58] imaging of draining LN instruments to measure and assess the lymphatic pulse are now available providing a unique opportunity to examine the diagnostic and prognostic potential of these biomarkers. Moreover, elucidation of the mechanism of efferent LN collapse may catalyze new drug development to specifically target lymphatics in a population of RA patients with advanced disease for whom effective therapies are limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, we predict that RA flares that take place sporadically in patients with chronic disease are associated with the loss of lymphatic egress from joints, and can be assessed by “collapsed” efferent LN and the absence of a lymphatic pulse. With the recent development of clinical PD-US [41] and NIR-ICG [58] imaging of draining LN instruments to measure and assess the lymphatic pulse are now available providing a unique opportunity to examine the diagnostic and prognostic potential of these biomarkers. Moreover, elucidation of the mechanism of efferent LN collapse may catalyze new drug development to specifically target lymphatics in a population of RA patients with advanced disease for whom effective therapies are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there are benefits to using a more cost-effective technique, such as ultrasound (US). Others have demonstrated that US can be used to monitor changes in the LN of RA patients undergoing treatment [41], and we have demonstrated that US is comparable to CE-MRI for determining relative PLN volume in mice [42]. Power Doppler (PD) is an US technique that can be used to observe blood flow in various tissues.…”
Section: Use Of Ultrasound For Pln Phenotypingmentioning
confidence: 99%
“…Former histologic studies on lymph node biopsies from different anatomic sites in established RA described follicular hyperplasia and interfollicular plasmacytosis [85] as well as increased GCs with high B-cell activity [86]. More recent data exploiting power Doppler ultrasound demonstrated the possibility to capture significant structural and vascular flow changes in axillary lymph node of patients with active disease, including hypertrophy of cortical regions [87]. Supporting these data, flow cytometry analysis of inguinal lymph node cells isolated from ultrasound-guided biopsies in in early arthritis patients showed an increase in activated CD69+ CD8+ cells and CD19+ B cells compared to healthy controls, suggesting an increased immune cell activation within the lymph node compartment [88].…”
Section: B Cells In Different Compartmentsmentioning
confidence: 99%
“…Taken together, these studies are consistent with a model in which the TNF-induced inflammatory cascade leads not only to localized effects in the targeted joints, but also to more regional effects on lymphatic vessels, lymph node histology, cellular composition and lymphoid subset function that directly contribute to chronic disease progression and flares. Structural and functional changes in draining lymph nodes, and pre-clinical alterations in resident cell populations are beginning to be recognized in RA patients, suggesting that these observations may be translatable to human disease [1820]. …”
Section: Discussionmentioning
confidence: 99%